Efficacy and risk factor assessment of outcomes of self-expanding metal stents deployed in advanced oesophageal cancer: a case series of 69 patients from a tertiary referral centre of South India - Siddiraju, Venkata Kapil Kishore; K. V., Ashok Kumar; N. S., Nagesh (International Surgery Journal, 2021)
Background: In India, Oesophageal cancer ranks as the 6th most common cause of cancer-related deaths. SCC is the most common histology with middle and lower third of the oesophagus as most common location. Often, it is diagnosed in elderly individuals with multiple comorbidities, and at an advanced stage with malignant strictures, where SEMS is treatment of choice. The current retrospective study aims to evaluate efficacy and the risk factor assessment of outcomes of SEMS deployment in patients with advanced oesophageal cancer. Methods: All consecutive patients referred to Department of SGE and LT of BMCRI, with advanced oesophageal cancer from March 2012 to October 2019 were studied. Patients details viz. demography, dysphagia grade, stricture details and SEMS related adverse events and 30-day, 90-day and long-term mortality data was charted and significance of these study parameters along with survival analysis was carried out by using relevant statistical tools. Results: Of the 69 patients, SCC in mid-oesophagus was the most common presentation. 36 patients (52.2%) received prior CRT, TEF (n=11) and distant metastasis (n=7). SEMS intention was palliation in all patients. Overall procedural success using ’Endoscopy alone’ was achieved in all 69 patients (100%). Post SEMS period uneventful (n=36), transient haemorrhage (n=5) patients, aspiration (n=11), tumour overgrowth and ingrowth (n=11), SEMS on SEMS (n=5), double SEMS for TEF (n=2). Significant adverse events necessitating reinterventions were seen in 17 patients (24.5%). Kaplan-Meier graph showed lower survival in patients with metastasis and TEF and no statistical difference in-terms of adverse events was noted based on fully covered versus partially covered SEMS. Conclusions: SEMS aids in early resumption of oral feeds and the outcomes of fully covered and partially covered SEMS are comparable in a palliative setting.